MEASURING THE PROCESS OF INTEGRATING ARTIFICIAL INTELLIGENCE TOOLS INTO THE PROFESSIONAL ACTIVITIES OF COMPUTER SCIENCE TEACHERS - Mubarakov, A.M.; Duisegaliyeva, A.D.; Baibaktina, A.T.; Kaipova, A.D. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
This study was devoted to the study of the process of integrating artificial intelligence (AI) tools into the professional activities of teachers. Since the purpose of the study is to identify the relationship between the age of teachers and their approach to the use of AI in educational practice, the results of a pilot study conducted among computer science teachers in Aktobe region schools in the 2024-2025 academic year are analyzed. As determined by the results of the study, the dependence of the problem of using AI on its perception by teachers of different generations, the level of training, and the propensity to allocate time resources is shown. The reason why teachers of the younger generation positively perceive the possibilities of AI, while teachers of the older generation are reluctant to accept them, was based on doubts that technology could reduce the role of teachers or lead to the destruction of the human factor in learning. Therefore, the importance of training future teachers to use AI tools in higher education institutions and the need to organize advanced training courses for school teachers is substantiated, and the amount of choice of respondents that should be covered in the course of research in the future is calculated.